Development of an Emergency Clinical Handover Tool for Doctors Using the Fuzzy Delphi Method - Mohd Saiboon, Ismail; Ibrahim, Ahmad Khalil; Mustafa, Abdul Karim; Jaafar, Mohd Johar; Isa, Mohd Hisham (Malaysian Journal of Medical Sciences, 2026)
Background: Clinical handover in emergency departments (EDs) is a critical, high-risk process, and miscommunication can lead to serious patient harm. Although the Introduction, Situation, Background, Assessment, Recommendation (ISBAR) framework is widely adopted to guide handovers, Malaysia currently lacks a validated and standardised tool specifically designed for ED settings. This gap underscores the need for a structured approach to ensure safer, more consistent patient transitions.Methods: To develop a new emergency clinical handover (ECH) tool, the Fuzzy Delphi Method (FDM) was employed with input from a panel of emergency physicians (EPs). A deductive approach was used to extract potential handover items, which were then rated on a 7-point Likert scale. These ratings were converted into triangular fuzzy numbers. Items were retained if they met three criteria: i) threshold value (d) ≤ 0.2; ii) expert agreement ≥ 75%; and iii) fuzzy score (A) ≥ 0.5. Perceptions of the proposed ECH tool were evaluated using a 10-item, 3-point Likert scale by the ED doctors after a one-month trial in a real-world ED situation.Results: The expert panel agreed on 19 items for inclusion in the ECH tool. These items were distributed across the ISBAR domains: five in Identification/Information, two in Situation, two in Background, seven in Assessment/Action, and three in Recommendation. The perception score indicated an acceptance rate of 70.17% among participants.Conclusion: The FDM effectively facilitated consensus in developing a structured ECH tool. This standardised approach may enhance communication, reduce variability, and improve patient safety during ED handovers.